Phytochemical Characterization of Sargassum swartzii (Turner) C. Agardh using TLC, FTIR and HPLC - Petchiammal E, Johnson M (Journal of Medicinal Herbs and Ethnomedicine, 2015)
The present study was aimed to investigate the phytochemical properties of Sargassum swartzii (Turner) C. Agardh. The standard method was employed to detect the metabolites presence or absence in the tested extracts of Sargassum swartzii. To confirm the occurrence of the functional constituents in the crude extracts of S. swartzii, spectroscopic UV-Vis and FT-IR analysis and chromatographic TLC and HPLC analysis were performed. The preliminary phytochemical analysis of S. swartzii displayed the existence of alkaloids, steroids, phenolic groups, saponins and flavonoids. TLC profile of S. swartii chloroform extract illustrated three phenolic bands with different Rf values 0.258, 0.777 and 0.879 and only one distinct steroid band was observed in the chloroform extract of S. swartii with the Rf value 0.724. Methanolic extracts of S. swartzii showed five compounds (peaks) with different retention time 1.960, 2.143, 2.303, 2.610 and 10.80 min. The HPLC chromatogram of S. swartzii chloroform extracts displayed six compounds (Peaks) with different retention time 1.983, 2.143, 2.280, 2.623, 3.500, 13.147 min. The results of FTIR analysis validated the occurence of functional groups such as alkynes, phosphorus compounds, unsaturated oximes, alcohols or phenols and halogen compounds in S. swartzii. The results of the present study confirmed that S. swartzii mayÂ be Â pool of natural metabolites further isolation may be bring out the novel biopotential compound with various biological activities.